Kathleen McCaughey and Dave McCaughey interviewed by Dave De Hugard in the Dave De Hugard collection of recordings with Kathleen McCaughey, February 1989 - McCaughey, Kathleen, 1901-; McCaughey, Dave.; De Hugard, Dave, 1942- (1989)
Folkloric recording of Dave and Kathleen "Narnie" McCaughey.
Recorded on February 1989.
Digital master available
Keywords: McCaughey, Kathleen, -- 1901- -- Interviews; McCaughey, Dave -- Interviews; Folk musicians -- Australia -- Interviews; Folk songs -- Australia; Folk music -- Australia; Folklore -- Australia; Accordion music -- Australia; Folk musicians